he expression \( 8^{\frac{3}{3}} \times 6^{2} \times\left(\frac{3}{2}\right)^{-4} \) is equivalent to \( 2^{a} \times 3^{b} \). Enter a number in each box \( =\square \) \( =\square \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Mind Expander
Let’s simplify the expression \( 8^{\frac{3}{3}} \times 6^{2} \times\left(\frac{3}{2}\right)^{-4} \). 1. **Simplifying \( 8^{\frac{3}{3}} \)**: \[ 8^{\frac{3}{3}} = 8^1 = 8 = 2^3 \] 2. **Simplifying \( 6^{2} \)**: \[ 6^2 = (2 \times 3)^2 = 2^2 \times 3^2 \] 3. **Simplifying \( \left(\frac{3}{2}\right)^{-4} \)**: \[ \left(\frac{3}{2}\right)^{-4} = \left(\frac{2}{3}\right)^{4} = \frac{2^4}{3^4} \] Now, combine all parts: \[ 8^{\frac{3}{3}} \times 6^{2} \times \left(\frac{3}{2}\right)^{-4} = 2^3 \times (2^2 \times 3^2) \times \left(\frac{2^4}{3^4}\right) \] Combining \( 2 \) terms: \[ 2^3 \times 2^2 \times 2^4 = 2^{3+2+4} = 2^9 \] And combining \( 3 \) terms: \[ 3^2 \times \frac{1}{3^4} = 3^{2-4} = 3^{-2} \] Putting it all together: \[ 8^{\frac{3}{3}} \times 6^{2} \times\left(\frac{3}{2}\right)^{-4} = 2^{9} \times 3^{-2} \] In the form \( 2^{a} \times 3^{b} \), we find: \[ a = 9, \quad b = -2 \] Thus, the answer is: \( =9 \) \( =-2 \)